Plantar pressure distribution in fencing shoes - Trautmann, C.; Rosenbaum, D. (ESM 2008 emed scientific meeting, 2008)
Fencing is a highly dynamic activity with specific and unique loading of the lower extremity. Up to now only a few publications have dealt with this issue. There are a few reports about psychological and medical aspects (2, 3, 4) as well as on biomechanical aspects and performance-related factors in fencing (1). Therefore, the aim of the present investigation was to evaluate plantar pressure distribution patterns in different fencing shoes in fencing-specific movements. These measurements deliver valuable information about the functional performance of the shoes.